1983
DOI: 10.1111/j.1365-2125.1983.tb01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of pindolol and propranolol on heart rate after acute and chronic administration.

Abstract: 1 The present study compared the effects in healthy volunteers of the acute and chronic administration of placebo, pindolol and propranolol to see if the partial agonist activity of pindolol was reduced by the ,8-adrenoceptor blocking activity of pindolol on chronic administration.2 Five subjects received in random order for 8 days placebo, propranolol 160mg and pindolol 10mg; on days 1 and 8 treatments were given twice at 0 and 2 h. Heart rate in supine position and at end of exercise was recorded before dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…P-adrenoceptor antagonists with PAA reduce resting heart rate less than drugs devoid of PAA (Finch et al, 1983;Svendsen et al, 1981;Gugler et al, 1980). The lack of effect of Ro31-1118 on resting supine heart rate, which was reduced by atenolol, is suggestive of PAA, which animal studies have shown is a feature of Ro3l-1118 pharmacology (Blaber et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…P-adrenoceptor antagonists with PAA reduce resting heart rate less than drugs devoid of PAA (Finch et al, 1983;Svendsen et al, 1981;Gugler et al, 1980). The lack of effect of Ro31-1118 on resting supine heart rate, which was reduced by atenolol, is suggestive of PAA, which animal studies have shown is a feature of Ro3l-1118 pharmacology (Blaber et al, 1983).…”
Section: Discussionmentioning
confidence: 99%